Flavonoid C-glucosides Derived from Flax Straw Extracts Reduce Human Breast Cancer Cell Growth In vitro and Induce Apoptosis - Czemplik, Magdalena; Mierziak, Justyna; Szopa, Jan; Kulma, Anna (Frontiers in Pharmacology, 2016)
Flax straw of flax varieties that are grown for oil production is a byproduct which represents a considerable biomass source. Therefore its potential application for human use is of high interest. Our research has revealed that flax straw is rich in flavonoid C-glucosides, including vitexin, orientin and isoorientin. The objective of this study was to evaluate the cytotoxicity and possible proapoptotic effect of flax straw derived C-glucosides of flavonoids in the human breast adenocarcinoma cell line (MCF-7). The effects of flax straw derived flavonoid C-glucosides on cell proliferation of MCF-7 cells were evaluated by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl-tetrazolium bromide (MTT) and sulforhodamine B (SRB) assays. The expression of apoptosis-related genes was assessed by real-time PCR. Our data revealed that flax C-glucosides as well as pure compounds are cytotoxic towards MCF-7 cells and inhibit their proliferation. Moreover, the induction of apoptosis was correlated with the changes in the mRNA level of pro-apoptotic genes. Increased expression of bax and caspase-7, -8, and -9 and decreased mRNA expression of bcl-2 was observed, whereas the mRNA levels of p53 and mdm2 were not altered. These results clearly demonstrated that flax straw metabolites effectively induced growth inhibition and apoptosis in human breast adenocarcinoma cells.